2021
DOI: 10.1002/acm2.13135
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diffusion‐weighted MRI and geometric distortion on a 0.35T MR‐LINAC at multiple gantry angles

Abstract: Diffusion-weighted imaging (DWI) provides a valuable diagnostic tool for tumor evaluation. Yet, it is difficult to acquire daily MRI data sets in the traditional radiotherapy clinical setting due to patient burden and limited resources. However, integrated MRI radiotherapy treatment systems facilitate daily functional MRI acquisitions like DWI during treatment exams. Before ADC values from MR-RT systems can be used clinically their reproducibility and accuracy must be quantified. This study used a NIST traceab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…By making a compromise between time and quality and limiting the number of b -values used for the calculation of the ADC maps to 2, it is possible to reduce the acquisition time to 78 s. This time reduction can be considered a satisfactory result since the duration of the typical diagnostic scanner sequences ranges from 40 s to 3–4 min depending on the need ( 35 ) and patient compliance ( 36 ). Our results in terms of stability analysis of ADC values as a function of averages are in line with those reported in a previous experience recently published ( 37 , 38 ). Since the results obtained for the variation of SNR and uniformity showed insignificance to minor deviations when varying slice thickness, we did not find it useful to proceed with an analysis of the stability of ADC coefficient values as a function of slice thickness.…”
Section: Discussionsupporting
confidence: 93%
“…By making a compromise between time and quality and limiting the number of b -values used for the calculation of the ADC maps to 2, it is possible to reduce the acquisition time to 78 s. This time reduction can be considered a satisfactory result since the duration of the typical diagnostic scanner sequences ranges from 40 s to 3–4 min depending on the need ( 35 ) and patient compliance ( 36 ). Our results in terms of stability analysis of ADC values as a function of averages are in line with those reported in a previous experience recently published ( 37 , 38 ). Since the results obtained for the variation of SNR and uniformity showed insignificance to minor deviations when varying slice thickness, we did not find it useful to proceed with an analysis of the stability of ADC coefficient values as a function of slice thickness.…”
Section: Discussionsupporting
confidence: 93%
“…These results highlight again the longitudinal stability of the tested MR-Linac system, but suggest that for MR imaging experiments that are sensitive to small changes in B 0 , re-shimming should be performed after the gantry angle is changed. Further, our results suggest that imaging during gantry rotation could be susceptible to effects related to B 0 , which has been previously described in literature [31] and also might have implications for qMRI techniques acquired during treatment delivery [32]. Jackson et al found that imaging while rotating the gantry did not impact clinical imaging, but could affect EPI-based imaging techniques [33].…”
Section: Discussionsupporting
confidence: 67%
“…The good agreement between institutes is encouraging for multi-center studies involving stereotactic radiotherapy [35] and for qMRI techniques that are sensitive to spatial gradient non-linearity, such as diffusion-weighted MRI [36]. However, post-processing might be required to account for distortions related to long-term eddy currents generated from the diffusion-weighting gradients [32].…”
Section: Discussionmentioning
confidence: 79%
“…Repeatability measures, such as test-retest studies, should also be conducted wherever feasible. Publications from QIBA and consortia relevant to the imaging unit being used [ 71 , 95 , 96 ] should be sought and be used as a foundation for sequence and quality assurance program design.…”
Section: Reliability/variability Of Quantitative Imaging Biomarkersmentioning
confidence: 99%
“…For example, when designing protocols for ADC measurement, b-values should be chosen with care, consulting the literature for that machine [ 71 ], and consideration given to the characterization of ADC accuracy across the imaging space with subsequent ROIs chosen accordingly. Factors such as linear-accelerator gantry angle on hybrid MRI-linear accelerators add additional uncertainty [ 71 , 95 , 96 ] which require quantification.…”
Section: Reliability/variability Of Quantitative Imaging Biomarkersmentioning
confidence: 99%